PENGARUH VARIASI PENAMBAHAN LAPISAN MAGNET DAN JARAK CELAH UDARA ROTOR TERHADAP KINERJA MOTOR DC MAGNET PERMANEN - Sri Kurniati; Sudirman Syam (Universitas Nusa Cendana, 2022)
A rectangular NdFeB permanent magnet DC motor design has been made and tested experimentally. The use of rectangular permanent magnet rotor teeth made in layers aims to increase the torque of the DC motor. Measurement and testing of DC motor force and torque using a spring balance. In addition, the adjustment of the air gap and the addition of a magnetic layer were carried out to determine the performance of a DC motor with varying rotation. This DC motor design has eight poles with 150 turns per coil and an arrangement of 1-4 layers of permanent magnets with an air gap of 1-4 mm. The results showed that the more layers of permanent magnets with a smaller rotor and stator magnetic air gap, the greater the torque. In measuring the motor's torque with four layers of permanent magnets for an air gap of 1 mm with a field voltage of 50 Volts, the electrical-torque is 0.6910 N-m, and the mechanical-torque is 0.027 N-m at a speed of 780 Rpm. Then at a voltage of 60 Volts with the same air gap distance, an electrical-torque of 0.085 N-m is obtained and a mechanical-torque of 0.0293 with a speed of 860 rpm